Cover Image, Volume 176A, Number 2, February 2018. Issue 2 (15th January 2018) - Chen, Ming Hui; Choudhury, Sangita; Hirata, Mami; Khalsa, Siri; Chang, Bernard; Walsh, Christopher A.
Abstract : The cover image, by Ming Hui Chen et al., is based on the Original Article Thoracic Aortic Aneurysm in Patients with Loss of Function Filamin A Mutations: Clinical Characterization, Genetics, and Recommendations, DOI: 10.1002/ajmg.a.38580 .